NMR quantitative investigation on methane hydrate formation characteristics under different driving forces. (1st February 2020) - Ma, Shihui; Zheng, Jia-nan; Tian, Mengru; Tang, Dawei; Yang, Mingjun
Graphical abstract: Highlights: Simultaneous investigation on the gas-water consumption of methane hydrate formation. The formation process of methane hydrate under different driving forces were studied. The hydration numbers of methane hydrate under different conditions were determined. Abstract: Methane hydrate is an important energy source and a good form of methane storage and transportation. The limit of gas storage capacity in hydrates is still not clear. In this study, we employed a low-field nuclear magnetic resonance to study the gas-water consumption characteristics quantitatively at various formation conditions. Nine methane hydrate formation experiments of different temperatures pressures were conducted in porous media. The consumption of gas and water for hydrate formation displayed as asynchronous trend, due to the change in hydrate cage occupancy. The results indicated that higher pressures or lower temperatures improved both the amount of hydrate formation and the cage occupancy of hydrate. In addition, the driving forces affected the formation of methane hydrate more obviously under a lower temperature. Ultimately, the hydration number of methane hydrate under different driving forces were determined. This study is of great significance to the estimation of hydrate and gas capacity in the hydrate based technology application in methane storage and transportation.